“Diagnóstico del clima laboral y su incidencia en el desempeño de la panadería “Ambato” del cantón Quevedo” - Muñoz Parraga, Mariana Melissa (2025)
The research focused on determining the impact of the work environment on the performance of the employees of the “Ambato” bakery in Quevedo, Ecuador. The bakery, a family business with several years in the local market, has experienced a decline in the performance of its employees. To diagnose the problem, symptoms such as low productivity, high employee turnover, absenteeism, interpersonal conflicts, low motivation and frequent complaints were identified. The causes of these symptoms were attributed to lack of recognition, poor communication, inadequate working conditions, lack of development opportunities, low salaries, and ineffective leadership. The overall objective of the research was to determine the impact of work climate on employee performance. A mixed research methodology was used, combining qualitative (interviews) and quantitative (surveys) methods. Documentary, descriptive, correlational and illustrative research methods were applied. Primary data (surveys, interviews and observation) and secondary data (scientific articles, books, websites and databases) were collected. A non-experimental, descriptive and correlational research was designed. A questionnaire based on the Likert scale, a satisfaction survey and a semi-structured interview were used as research instruments. The results revealed that the work climate has a significant impact on employee performance. Areas for improvement in communication and customer service were identified, as well as key factors that impact the work climate, such as lack of recognition and the need to set clear goals. It was concluded that it is crucial to continually evaluate the effectiveness of these strategies and adapt them to the changing needs of the staff and the market.